2013
DOI: 10.1021/la402777e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Mesoscopic Materials To Form Controlled and Continuous Patterns by Thermo-Optically Manipulated Laser Induced Microbubbles

Abstract: The formation of continuous patterns of nanostructured materials using directed self-assembly under external fields has generated considerable current research interest. We demonstrate for the first time such continuous patterning by inducing irreversible self-assembly leading to nucleation in mesocopic materials (inorganic, organic, and nanoparticles) using a tightly focused laser beam in an optical tweezers apparatus. A dense aqueous dispersion or solution of the material which has high absorption at the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
134
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(139 citation statements)
references
References 43 publications
4
134
1
Order By: Relevance
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by us and others that each of the components of the above host-guest species [PMo 12 @Mo 72 Fe 30 ] i.e., PMo 12 and Mo 72 Fe 30 independently shows superstructured soft-oxometalate (SOM) formation by spontaneous assembly in colloidal lengthscales. 1,2,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We have previously shown that a dilute sonicated dispersion of PMo 12 leads to the formation of peapod 37 like SOM structures. Initially, the peapods have nanosphere-type morphology and with time these spheres get converted to nanorods with nanospheres embedded inside this rod.…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65][66] 68 Now we ask, is it possible to synthesize a polyoxometalate in turn a soft oxometalate (SOM). [69][70][71][72][73] which can generate oxygen from water photo-chemically?…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalate units self-assemble in dispersion to form super structures which are known as soft oxometalates (SOMs). 70,74,75 We have explored di®erent properties of soft oxometalates over the last few year. [76][77][78] Soft oxometalates can under-go topological transformation in the presence of light.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of QDs' structures under optical irradiation due to various non-electrodynamical mechanisms were studied, e.g. in [11][12][13]. Surprisingly, no experimental attempts were done up to date to perform electrodynamically-driven laser-induced self-assembly of semiconductor nanoparticles, that may be of interest for quantum information, spintronics, single-electron transport, and sensoric devices.…”
Section: Introductionmentioning
confidence: 99%